BDNF rs6265 polymorphism and drug addiction: a systematic review and meta-analysis. (December 2013) - Haerian, Batoul Sadat
A majority of studies have shown a link between the common functional rs6265 polymorphism of the BDNF gene and susceptibility to drug dependence. However, the pattern of results is inconsistent. To precisely evaluate this association, a systematic review and meta-analysis of previous case–control reports was conducted. Data from 20 studies containing 9419 participants (4665 cases and 4754 controls) conducted between 2004 and 2013 restricted to alcohol, nicotine, heroin, substance and methamphetamine dependency were meta-analyzed. Following quality control of the results, a significant association between C allele and methamphetamine dependence remained in south Asian subjects (p = 0.004). Similar results were detected in south Asian subjects for methamphetamine dependence and in Chinese subjects for heroin dependence under an autosomal codominant genotype model (TT vs CC, p = 0.005 and p = 0.0004, respectively). In conclusion, the rs6265 polymorphism may be a risk factor for methamphetamine dependence in south Asian subjects or for heroin dependence in Chinese subjects.